Outdoor lighting: sustainable practices for effectively restoring the night - Kinder, Bailey (My University, 2024)
Artificial lighting at night has lasting negative impacts on humans, animals, and the environment. This report aims to review and analyze existing and emerging sustainable practices in outdoor lighting that can aid in effectively restoring the night. The analysis of this report is focused on lighting quality metrics and sustainability. Other issues are discussed briefly but the main focus of this report is night sky issues. Through a comprehensive literature review and empirical analysis, the causes, effects, and potential solutions to light pollution are discussed. A review of current standards, codes, and guidelines is also included. Furthermore, an example demonstrating the recommended design goals discussed throughout the report is detailed. This report finds there is a vast potential for drastic energy conservation within exterior lighting design utilizing the combination of emerging technologies for a comprehensive, adaptable solution to better protect the night sky. This research analyzes the trajectory of the industry and how to best apply the tools at designers’ disposal. The findings of this report can be used both to guide individual lighting design as well as to help further the path that standards and committees are trying to pave in order to effectively minimize light pollution and its effects.
Keywords: Outdoor lighting; Exterior lighting; Sustainability; Lighting design; Artifical lighting at night; Dark sky